2015
DOI: 10.1016/j.virol.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts both in cellular membrane and viral envelope are critical for PRRSV efficient infection

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) represents a significantly economical challenge to the swine industry worldwide. In this study, we investigated the importance of cellular and viral lipid rafts in PRRSV infection. First, we demonstrated that PRRSV glycoproteins, Gp3 and Gp4, were associated with lipid rafts during viral entry, and disruption of cellular lipid rafts inhibited PRRSV entry. We also showed the raft-location of CD163, which might contribute to the glycoproteins-raft assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…The transfected PK-15 cells were inoculated with PRRSV strain BJ-4 at a multiplicity of infection (MOI) of 1 at 37°C for 3 h. The viruses not entering into the cells were washed away with sterile culture medium. PPRSV infection was then analyzed by quantitative real-time PCR at 12 h postinoculation (38). Briefly, total RNA from infected PK-15 cells was extracted with TRIzol reagent (Ambion).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transfected PK-15 cells were inoculated with PRRSV strain BJ-4 at a multiplicity of infection (MOI) of 1 at 37°C for 3 h. The viruses not entering into the cells were washed away with sterile culture medium. PPRSV infection was then analyzed by quantitative real-time PCR at 12 h postinoculation (38). Briefly, total RNA from infected PK-15 cells was extracted with TRIzol reagent (Ambion).…”
Section: Methodsmentioning
confidence: 99%
“…For PRRSV binding assay (38,39), the transfected cells were inoculated with PRRSV strain BJ-4 or HN07-1 at an MOI of 1 and incubated at 4°C for 1 h. After the unbound viruses washed away, the level of cell-bound viral RNA (PRRSV ORF7) was normalized with housekeeping glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA and relatively quantified by the 2 ϪΔΔCT method. For PRRSV entry assay (38,39), the unbound viruses were washed away and the inoculated cells were then transferred to 37°C for 3 h to allow virus entry. The viruses not entering into the cells were washed, and the entering viral RNA was analyzed by the 2 ϪΔΔCT method similarly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, MβCD were used to deplete cholesterol in our study. MβCD were most commonly used to deplete cholesterol from cell membrane in the studies of lipid rafts . In our study, we also used MβCD to remove cholesterol and the results here showed that MβCD can reduce cholesterol in treated cells significantly with dose‐dependent.…”
Section: Discussionmentioning
confidence: 59%
“…Among the nonstructural proteins, Nsp9 contains an RNA-dependent RNA polymerase (RdRp) domain in its C-terminal portion, which is critical for viral RNA synthesis, and replication efficiency (Fang and Snijder, 2010;Yang et al, 2015;Zhou et al, 2011). In this regard, recent advances show that amino acids at positions 519, 544, 586 and 592 in Nsp9 contribute to enhanced pathogenicity and determine the fatal virulence of the virus Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%